Implementasi Algoritme Naive Bayes Menggunakan Arduino Uno untuk Otomatisasi Lampu Ruangan Berdasarkan Kebiasaan dari Penghuni Rumah - Septian Mukti Pratama; Wijaya Kurniawan; Hurriyatul Fitriyah (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Lamps are the equipment that must be owned in every home because the lights has an important role in everyday life. The lamp are very helpful to the home owner to do the activities in the house by lighting up the entire room inside the house, especially as the sun began to sink. This study aims to help residents at home in controlling the lights by doing automation of lights that can learn the behavior of the residents in turning on and turning off the lights. This study uses Naive Bayes algorithm to classify the time turn on or off light based on the user's habits in turning on and off the lights. The result of the classification process will result in the time of automation the lamp. The Naive Bayes method was chosen as one of the techniques for classification, because this method requires only a small amount of training data to estimate the parameters required for classification. In addition, in this study using Arduino Uno microcontroller to apply the process of automation of lamps and RTC to adjust in Real Time. From the results of several tests performed known the percentage of accuracy on the system using Naive Bayes method with the amount of data train as much as 40 data and test data of 13 data, obtained accuracy of 84.61% for the first person and 92.30% in the second. Average processing time for 0.25 seconds from 13 test.